A Tailored Versatile and Efficient NHC‐Based NNC‐Pincer Manganese Catalyst for Hydrogenation of Polar Unsaturated Compounds - Wei, Zeyuan; Li, Hengxu; Wang, Yujie; Liu, Qiang (Angewandte Chemie, 2023)
The reactivity of metal‐hydride complexes can be harnessed by the modification of ancillary ligands. With the aim of improving the hydride‐donor ability of the key Mn−H intermediate and reducing steric hindrance, we herein report the rational design of a versatile and efficient NHC‐based NNC‐pincer Mn catalyst for hydrogenation reactions. This newly developed catalyst exhibited higher activity than the corresponding NNP‐pincer Mn catalyst owing to its reduced steric hindrance and enhanced Mn−H σ‐bonding orbital energy level through a π‐antibonding interaction. Using this highly active NNC‐pincer Mn catalyst, a rich array of polar unsaturated compounds (>80 examples) including esters, N‐heteroarenes, amides, carbonates, and urea derivatives, were successfully hydrogenated under relatively mild conditions. This work represents a rare example of a general phosphine‐free Mn‐catalyzed hydrogenation system. The hydride‐transfer reactivity of Mn‐hydride species has been greatly enhanced via rational design of a strong electron‐donating and sterically unhindered NHC‐based NNC‐pincer ligand. This newly developed NNC‐pincer Mn catalyst is highly effective for the hydrogenation of a broad range of polar unsaturated compounds (>80 examples) including esters, N‐heteroarenes, amides, carbonates, and urea derivatives, under relatively mild conditions.